Effectiveness of Leininger's Transcultural-based GATHER Counseling Model on Exclusive Breastfeeding - I Gusti Ayu Karnasih (Humanistic Network for Science and Technology (HNST), 2021)
Objective: to analyze the effectiveness of Leininger’s Transcultural-based GATHER (Greet, Ask, Tell, Help, Explain, and Return/refer) Counseling Model for exclusive breastfeeding. Methods: The experimental research was conducted with the post-test only control group design. The sample size of control group and treatment group were 38 people. The sampling technique is a simple random sampling technique. The treatment group were third stage III pregnant women with a gestational age of 36-37 weeks and at the second day postpartum. Data were collected using questionnaires and observations of 76 breastfeeding mothers in Jember Regency, then analyzed using Mann Whitney-U test. Results: The results showed that postpartum mothers who were given Leininger's Transcultural-based GATHER Counseling Model showed a higher percentage of exclusive breastfeeding (81.1%) than postpartum mothers who were not given counseling (21.6%). The results of hypothesis testing showed p-value of 0.000, meaning that the hypothesis was accepted so that it could be said that exclusive breastfeeding for mothers who were given counseling was higher than those who were not given Leininger's Transcultural-based GATHER Counseling Model and it was effective in increasing milk production. Conclusion: Leininger's Transcultural-based GATHER Counseling Model is effective in increasing exclusive breastfeeding, this model facilitates understanding and management of the factors that cause problems, breastfeeding. Keywords: exclusive breastfeeding; GATHER counseling model; Leininger’s transcultural model